An Investigation into the Impact of E-Customs on Stretching Strategic Thinking - Salamzadeh, Yashar; Nejati, Mehran; Heidaripourafshar, Yahya (Journal of Entrepreneurship, Business and Economics, 2015)
Challenges facing the customs organization continuously change its management system in different countries and customs managers face a large number of challenges. Globalization tendencies, in-creased technological developments, customer-orientation, decreased product life cycle, change in product nature, regionalism and competition diversity demand a new form of leadership. The manag-ers, therefore, need to be prepared for administrating changes in dynamic environments. On the other hand, the organizations should also take the necessary actions in order to change and improve the current procedures; otherwise, they will jeopardize their existence and perpetuity because today the existence of organizations is threatened more than ever before. Considering the difficulties and bot-tlenecks of strategic planning, strategic thinking is used today as an important instrument assisting managers to solve problems and promote competitiveness and dynamics. The aim of this study is to investigate the impact of establishing e-customs on stretching strategic thinking. It is a survey study in terms of method where the statistical population is composed of all technical experts of IRICA in 2015, i.e. a total number of 650 cases 234 of which were selected through simple-random sampling using Krejcie and Morgan method. Data was collected using a researcher-made questionnaire. Its validity was confirmed through formal validation and its reliability was calculated using Cronbach’s alpha (0.726). All data was analyzed in SPSS 19. According to data analysis results, e-customs affects strategic thinking dimensions with a different influence on every dimension. The results showed that the impact of establishing e-customs on systems thinking, creativity, conceptual thinking, intelligent opportunism, and foresight was 15%, 17%, 17%, 13%, and 22%, respectively. Hence, it is proposed that managers pay special attention to foresight and then to creativity and conceptual thinking in or-ganizations. Research paper Reference to this paper should be made as follows: Salamzadeh, A., Nejati, M., & Heidaripourafshar. Y. (2015). “An Investigation into the Impact of E-Customs on Stretching Strategic Thinking (Case Study: Islamic Republic of Iran Customs Administration (IRICA))”, Journal of Entrepreneurship, Business and Economics, Vol. 3, No. 1, pp. 105–139.